Variable effects on growth and defense traits for plant ecotypic differentiation and phenotypic plasticity along elevation gradients - Bakhtiari, Mojtaba; Formenti, Ludovico; Caggìa, Veronica; Glauser, Gaëtan; Rasmann, Sergio (My University, 2019)
Along ecological gradients, phenotypic differentiation can arise through natural selection on trait diversity and magnitude, and environment‐driven plastic changes. The magnitude of ecotypic differentiation versus phenotypic plasticity can vary depending on the traits under study. Using reciprocal transplant‐common gardens along steep elevation gradients, we evaluated patterns of ecotypic differentiation and phenotypic plasticity of several growth and defense‐related traits for two coexisting but unrelated plant species, Cardamine pratensis and Plantago major. For both species, we observed ecotypic differentiation accompanied by plasticity in growth‐related traits. Plants grew faster and produced more biomass when placed at low elevation. In contrast, we observed fixed ecotypic differentiation for defense and resistance traits. Generally, low‐elevation ecotypes produced higher chemical defenses regardless of the growing elevation. Yet, some plasticity was observed for specific compounds, such as indole glucosinolates. The results of this study may suggest that ecotypic differentiation in defense traits is maintained by costs of chemical defense production, while plasticity in growth traits is regulated by temperature‐driven growth response maximization.